2011
DOI: 10.1073/pnas.1109879108
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Akt kinases to dephosphorylation through ATP-dependent conformational plasticity

Abstract: Phosphorylation of a threonine residue (T308 in Akt1) in the activation loop of Akt kinases is a prerequisite for deregulated Akt activity frequently observed in neoplasia. Akt phosphorylation in vivo is balanced by the opposite activities of kinases and phosphatases. Here we describe that targeting Akt kinase to the cell membrane markedly reduced sensitivity of phosphorylated Akt to dephosphorylation by protein phosphatase 2A. This effect was amplified by occupancy of the ATP binding pocket by either ATP or A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 42 publications
(55 reference statements)
6
99
0
Order By: Relevance
“…2). 10 However, all Mek1/Mek2 crystal structures available to date have been generated without activation loop phosphorylation. 30,31 Collectively, these observations raise the intriguing possibility that allosteric control of phosphatase access to activation loop…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2). 10 However, all Mek1/Mek2 crystal structures available to date have been generated without activation loop phosphorylation. 30,31 Collectively, these observations raise the intriguing possibility that allosteric control of phosphatase access to activation loop…”
Section: Resultsmentioning
confidence: 99%
“…Mutational analysis confirmed that arginine 273 (arginine 274 in Akt2) and histidine 194 in Akt1 were required to inhibit threonine 308 dephosphorylation. 10 The product of ATP hydrolysis, ADP and the ADP-βS analog, were markedly less effective in blocking dephosphorylation. 10 All-atom molecular modeling and molecular dynamics (MD) simulations of ATP vs. ADP binding in Akt kinase revealed that the histidine 194/phospho-threonine 308 interaction is by an intra-molecular mechanism that controls dephosphorylation kinetics of the activation loop in AGC kinases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve increased transport of GFP to cellular membranes, we added a myristoylation signal (Chan et al, 2011;Maurer-Stroh et al, 2002), and for nuclear localization we tagged the GFP with a specific nuclear localization signal that translocates GFP to the cell nucleus (Fig. 1b).…”
mentioning
confidence: 99%
“…This conclusion is based on the following results: 1) ADP-mediated protection is observed in the Snf1-L183I kinase in the complete absence of a ␥ subunit; 2) staurosporine, a compound known to bind to kinase active sites, affords strong protection of Snf1 from dephosphorylation; and 3) the adenosine analog 2NM-PP1 mediates protection from dephosphorylation only to the analog-sensitive form of Snf1 containing an amino acid substitution in its active site. The ability of adenylate nucleotides bound in a kinase active site to mediate protection of the activation loop from dephosphorylation has recently been described for the mammalian AKT kinase (40,41).…”
Section: Discussionmentioning
confidence: 99%